Computer Aided Arabic Language Learning: A Systematic Review of Technology Integration and Effectiveness - Hasyim Asy'ari; Taufik Siraj; Elok Rufaiqoh; Muhammad ‘Ainul Yaqin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to systematically analyze Computer-Aided Arabic Language Learning, evaluate its effectiveness based on empirical evidence, identify the underlying theoretical framework, and map the challenges and opportunities for its implementation. This study uses the Systematic Literature Review method by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guide. An analysis was conducted on 86 articles discussing Computer-Aided Arabic Learning from theoretical, technological, and implementive aspects published from 2015 to 2025. Key findings show that Computer-Aided Arabic Learning, supported by frameworks such as Computer-Assisted Language Learning and Technological Pedagogical Content Knowledge, significantly improves students' motivation and learning outcomes. Modern apps have evolved from just tools to adaptive tutors, characterized by the ability of apps to continuously analyze user learning data and personalize materials, difficulty levels, and feedback, rather than simply presenting the same static exercises for all students and often leveraging gamification and artificial intelligence to create personalized learning experiences. However, its effectiveness is limited by substantial challenges, including infrastructure gaps, educators' digital competence, limitations of formal evaluations for productive skills (speaking and writing), and the linguistic complexity of Arabic that has not been fully addressed by current technology. Computer-Aided Arabic Learning is a powerful pedagogical accelerator, but its potential can only be maximized through a strategic approach that integrates technology development with educator capacity building and the adoption of blended learning models. Synergy between academic innovation and practical implementation is needed to overcome existing challenges and realize the full potential of technology in Arabic language education.